Recombinant expression and purification of squid suckerin-spider silk fusion proteins for formation of thermosensitive hydrogel and biomimetic production of silk fibers - Koh, Kenrick Yee Hong (2018)
The suckerin from giant squid Dosidicus gigas and the spider silk are both protein-based biomaterials with remarkable mechanical properties, and thus they have great potential for the engineering of new biomimetic materials, such as fibers and thermosensitive hydrogels for biomedical applications. However, development of these applications requires robust recombinant expression systems that allow for production of high amount of spider silk and suckerin proteins. So far, efficient recombinant production of these proteins has been difficult to achieve due to their primary sequence characteristics i.e. high hydrophobicity and modular repeats that decrease their solubility. Recent studies have showed that these issues can be overcome by using a chimeric spider silk protein and shortening the repetitive sequences. Using this approach, we designed novel spider silk-squid suckerin fusion proteins. We successfully expressed and purified these proteins, and achieved a high production-yield of up to 154mg/L. Moreover, we demonstrated that the fusion proteins are capable of thermosensitive gelation to form hydrogels with tunable properties, making them an attractive application for biomedical scaffolds. We also attempted to biomimetically create mechanically stronger fibers using the fusion proteins.